2015
DOI: 10.1007/s00417-015-3168-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flavonoids on visual function in patients with glaucoma or ocular hypertension: a systematic review and meta-analysis

Abstract: Meta-analyses showed that flavonoids have a promising role in improving visual function in patients with glaucoma and ocular hypertension (OHT), and appear to play a part in both improving and slowing the progression of visual field loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 23 publications
4
30
0
Order By: Relevance
“…Dietary antioxidants have a key role in oxidative stress reduction by inhibiting oxidative reactions and removing free radical intermediates [24]. Our findings of higher dietary intake of vitamin C and reduced outcomes of glaucoma, cataracts, and age-related macular degeneration are consistent with findings from previous studies [25,26,27,28,29]. β-carotene was also identified to reduce the risk of oxidative stress-related eye diseases with higher dietary intake.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Dietary antioxidants have a key role in oxidative stress reduction by inhibiting oxidative reactions and removing free radical intermediates [24]. Our findings of higher dietary intake of vitamin C and reduced outcomes of glaucoma, cataracts, and age-related macular degeneration are consistent with findings from previous studies [25,26,27,28,29]. β-carotene was also identified to reduce the risk of oxidative stress-related eye diseases with higher dietary intake.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, trivial or unclear associations were found between the consumption of flavonoids and the incidence of ocular disease, in contrast to emerging data on the effect of flavonoid consumption on visual acuity in those with GLA [29]. The dietary consumption of flavonoids in the study population ranged from 0.15 to 2 g daily, which is similar to the values reported in the general population [3].…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…In the current issue of Graefe's Archive for Clinical and Experimental Ophthalmology, Patel et al evaluate the efficacy of flavonoids in glaucoma and ocular hypertension, performing a review and a meta-analysis of the currently published data, including only randomized controlled trials [8]. The number of included studies was surprisingly small: among the initially 16,840 screened articles, only six trials encompassing a total of 214 participants could be included, based on the inclusion criteria.…”
mentioning
confidence: 99%
“…A neuroprotective and microvascular effect of flavonoids may have played a role in this process, both at the ocular and cerebral level. In order to evaluate the effect of flavonoids on ocular blood flow, the same study [8] included a review of three reports (using different measurement methods, and therefore not submitted to meta-analysis). The review suggested a significant improvement of ocular blood flow (measured by laser Doppler flowmetry or by laser speckle flowgraphy) after flavonoid treatment.…”
mentioning
confidence: 99%